Driving development : a story of BRAC's evolution and effectiveness - Hossain, Mahabub, 1945-; Kairy, Shib Narayan; Bayes, Abdul (University Press Limited, 2016)
[The Bangladesh Rural Advancement Committee or] BRAC is now about 45 years old and this watershed moment provided an opportunity to reflect on the last four decades or so. More importantly, the aim is to look ahead for the challenges that would be confronted by BRAC. In the backdrop of these factors, this book inscribes the evolution of development interventions made by BRAC, including the mistakes made and the lessons learnt, in its efforts to contribute to socio-economic advancement of the country.--Publisher's website.